2008
DOI: 10.1021/jp0748213
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Stability from Variable Temperature FT-IR Spectra of Krypton Solutions, r0 Structural Parameters, Vibrational Assignment, and ab Initio Calculations of 4-Fluoro-1-butene

Abstract: Variable temperature (-115 to -155 degrees C) studies of the infrared spectra (3200-400 cm-1) of 4-fluoro-1-butene, CH2=CHCH2CH2F, dissolved in liquid krypton have been carried out. The infrared spectra of the gas and solid as well as the Raman spectra of the gas, liquid, and solid have also been recorded from 3200 to 100 cm-1. From these data, an enthalpy difference of 72 +/- 5 cm-1 (0.86 +/- 0.06 kJ x mol-1) has been determined between the most stable skew-gauche II conformer (the first designation refers to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…The structural and conformational properties of this class of compound, which are analogous to that of H 2 CCHCH 2 CH 2 NC, have received considerable attention in the past. One example is 4-fluoro-1-butene (H 2 CCHCH 2 CH 2 F), which has been studied several times. A conformer corresponding to III has been found to be the lowest energy form. Two additional forms with slightly higher energies were found in the gas-phase in a MW work, while all five forms were identified in a far-infrared study of a krypton solution . A gas electron diffraction (GED) and molecular-mechanics investigation of H 2 CCHCH 2 CH 2 Cl and H 2 CCHCH 2 CH 2 Br again showed that forms analogous to III are the most stable ones in these two cases and that there are minor contributions from other conformers .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structural and conformational properties of this class of compound, which are analogous to that of H 2 CCHCH 2 CH 2 NC, have received considerable attention in the past. One example is 4-fluoro-1-butene (H 2 CCHCH 2 CH 2 F), which has been studied several times. A conformer corresponding to III has been found to be the lowest energy form. Two additional forms with slightly higher energies were found in the gas-phase in a MW work, while all five forms were identified in a far-infrared study of a krypton solution . A gas electron diffraction (GED) and molecular-mechanics investigation of H 2 CCHCH 2 CH 2 Cl and H 2 CCHCH 2 CH 2 Br again showed that forms analogous to III are the most stable ones in these two cases and that there are minor contributions from other conformers .…”
Section: Introductionmentioning
confidence: 99%
“…11−13 Two additional forms with slightly higher energies were found in the gas-phase in a MW work, 12 while all five forms were identified in a far-infrared study of a krypton solution. 13 A gas electron diffraction (GED) and molecular-mechanics investigation of H 2 C CHCH 2 CH 2 Cl and H 2 CCHCH 2 CH 2 Br again showed that forms analogous to III are the most stable ones in these two cases and that there are minor contributions from other conformers. 14 The preferred form of H 2 CCHCH 2 CH 2 OH corresponds to II, and it is stabilized by an intramolecular hydrogen bond between the hydroxyl group and the π- electrons of the double bond.…”
Section: ■ Introductionmentioning
confidence: 99%